Burden, risk factors, and clinical outcomes of pediatric malaria in Nigeria: A systematic review and meta-analysis protocol - Olayinka Rasheed Ibrahim; Jubril Abdulkareem; Amudalat Issa; Michael Abel Alao (PLoS ONE, 2026)
Background Nigeria ranks number one globally in malaria burden, with the exact burden, especially for hospitalization, unknown. This systematic review and meta-analysis will pool laboratory-confirmed pediatric malaria data across Nigeria using standardized World Health Organization (WHO) case definitions and random-effects modeling to generate precise national and subgroup-specific estimates of prevalence, associated factors, and outcomes, thereby addressing a critical evidence gap. Methods and analysis A comprehensive search strategy using MeSH terms, text words, and entry terms will be applied across six databases: PubMed, Embase, EBSCOhost, Google Scholar, Web of Science, and Scopus. Eligible studies will be observational and interventional studies, without language restriction, from inception through June 30, 2025. Non-English studies will be translated using professional translation tools [Google Translate (academic mode) and Microsoft Translator] and verified by native speakers. The primary outcome is the pooled prevalence of pediatric malaria [overall, severe malaria vs. uncomplicated]. Secondary outcomes include factors influencing clinical presentation and outcomes, as well as the effects of moderators such as age, sex, socioeconomic status, and geographic location. Data extraction will capture study characteristics, participant demographics, and outcome measures. Methodological, clinical, and statistical heterogeneity will be assessed. Risk of bias will be assessed using the Newcastle-Ottawa Scale (NOS) adapted for observational studies, and the Cochrane Risk of Bias tool (RoB 2.0) for interventional studies. Publication bias will be examined using funnel plots and Egger’s regression. Pooled estimates will be reported with 95% confidence intervals. This will summarize the data on pediatric malaria in Nigeria. Using the random-effects models, the pooled prevalence, along with the 95% CI and the I 2 for the test of heterogeneity, will be reported. We will report the meta-regression analysis of factors influencing pediatric malaria in Nigeria. Conclusions This study will provide robust data on pediatric malaria and associated factors in Nigeria. The findings from this study will inform the country’s policy and public health approach as the nation strives to eliminate malaria in line with the WHO’s goals. PROSPERO Registration Number: CRD420251163322.